A CASE REPORT OF HIGH 18FFDG UPTAKE IN LEIOMYOMA OF THE ESOPHAGUS AND STOMACH - A. S. Subbotin; N. G. Afanasyeva; O. N. Chernova (Сибирский онкологический журнал)
Benign tumors of the esophagus and stomach are rare lesions and they usually present as leiomyomas. There have been no published reports indicating high metabolic activity of leiomyomas, detected by PET-CT. In the present case, gastric leiomyoma extending into the esophagus was found to have a high 18F-FDG uptake.